2016
DOI: 10.3390/w8050187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use Types on Community Structure Patterns of Benthic Macroinvertebrates in Streams of Urban Areas in the South of the Korea Peninsula

Abstract: Benthic macroinvertebrates were collected from streams located in an urban area from regions featuring different environmental conditions. Physicochemical variables and land use types pertaining to sampling sites were analyzed concurrently. Multivariate analyses (cluster analysis and non-metric multidimensional scaling) and rank-abundance diagrams were used to characterize community patterns to assess ecological integrity in response to environmental conditions. Species composition patterns were mainly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Among the several aquatic organisms present in streams or rivers, benthic macroinvertebrates have a differentiated functional form according to the given physical or chemical conditions. Thus, their species diversity is high and responds to changes in the various environmental variables (Jun et al 2016;Kim et al 2016). Based on these characteristics, benthic macroinvertebrates have been used as bioindicators for assessment of water quality and the health of aquatic environments (Rosenberg et al 1986;Smith et al 1999; Barman and Gupta 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the several aquatic organisms present in streams or rivers, benthic macroinvertebrates have a differentiated functional form according to the given physical or chemical conditions. Thus, their species diversity is high and responds to changes in the various environmental variables (Jun et al 2016;Kim et al 2016). Based on these characteristics, benthic macroinvertebrates have been used as bioindicators for assessment of water quality and the health of aquatic environments (Rosenberg et al 1986;Smith et al 1999; Barman and Gupta 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The pollution due to land use activities influences the ecological quality of river waters (Selvanayagam and Abril 2016). LM1, LM2, and LM3, located in the tributary upper river, is dominated by forest land use which has little disturbance, so they had abundant macroinvertebrates, a bioindicator of undisturbed areas (Azmi and Geok 2016;Kim et al 2016;dos Reis et al 2017). The Lahumoko's upstream watershed area is represented by LM1, LM2, and LM3, showing that Ephemeroptera Order's Heptageniidae family and Trichoptera Order's Goeridae family had been found.…”
Section: Biodiversity Of Aquatic Macroinvertebrates Communitiesmentioning
confidence: 99%
“…Many scrapper species are present at the land used for agriculture and settlements with high pollution which is related to the increased water volume and river width and substrate dominated Mud and Clay's (Rosenberg and Resh 1993;Fu et al 2016). Some shredder groups such as Ephemeroptera, Plecoptera, and Trichoptera on mountains and upstream area are sensitive to organic pollution and may serve as a river water bioindicator of unpolluted forest (Elias et al 2014;Kim et al 2016). The highest abundance is found in the upstream watershed and the lowest in the downstream which is characterized by flow velocities (Szczerkowska-Majchrzak and Grzybkowska 2015) and place heights according to river order, food and other environmental parameters (Jiang et al 2011;Fu et al 2016).…”
Section: Biodiversity Of Aquatic Macroinvertebrates Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [20] examined the effects of land use types on community structure patterns of benthic macroinvertebrates in streams of urban areas. They found that species composition patterns are mainly influenced by both the gradient of physicochemical variables such as altitude, slope, and conductivity, and the proportion of forest area.…”
Section: Contributionsmentioning
confidence: 99%